Evidências de vida no mundo dos mortos: o megalitismo do concelho de Arraiolos - Rocha, Leonor (2017)
During the last 150 years, archaeological research has been going through periods of significant stagnation, followed by periods of intense activity, more or less focused in specific areas, chronological periods and/or themes. The current Municipality of Arraiolos is a good example of this situation, especially in regards to the study of megalithism. The information presented in this study is mainly based on data collected during two of the most active periods; I) between 1931 and 1945, when Manuel Heleno drew up an inventory and excavated dozens of funerary megalithic monuments in this area; ii) since 2010 and until the present, with research projects coordinated by the author. The summary of the data collected up until the present has led us, now, to have a good notion of the life and death of the first agrarian societies which inhabited this region between around 6000 and 3000 b.C.